Enhancing the role of pragmatics in primary English teacher training - Glaser, Karen (Glottodidactica, 2018)
Teaching EFL in primary school is no longer a novelty but firmly established in the education landscape throughout Europe and many countries worldwide. Primary English language teaching (PELT) is a unique branch of ELT insofar as it entails both the teaching of children and beginners. While PELT teachers and PELT teacher educators largely agree that this concurrence of ‘young plus beginning’ requires a focus on vocabulary, speaking and listening, introduced and practiced through songs, games, stories, roleplaying and embodiment techniques such as Total Physical Response, pragmatic aspects often take a backseat in PELT teacher training and by extension in the PELT classroom, even though it has been established that pragmatics instruction is necessary and feasible on all proficiency levels, right from the beginning. This article discusses possible reasons for this omission and illustrates with authentic examples why pragmatics should play a bigger role in the training of primary English teachers.